Individualized luteal phase support in frozen-thawed embryo transfer after intramuscular progesterone administration might rectify live birth rate - Boynukalin, Fazilet Kübra; Tohma, Yusuf Aytac; Yarkıner, Zalihe; Gultomruk, Meral; Bozdag, Gürkan; Ozkavukcu, Sinan; Bahçeci, Mustafa; Demir, Berfu (Frontiers in Endocrinology, 2024)
Abstract Background: The serum P concentrations are suggested to have an impact on pregnancy outcome. However there is no consensus about the optimal progesterone cut-off during the luteal phase Few studies evaluated the effectiveness of a “rescue protocol” for low serum P concentrations and most of these studies used vaginal progesterone administration. There is paucity of data on the effectiveness of rescue protocol using intramuscular progesterone (IM-P) in frozen-thawed embryo transfer (FET). Methods: This study is a retrospective cohort study included 637 single or double blastocyst FETs with artificially prepared endometrium receiving 100 mg IM progesterone (P) after incremental estrogen treatment. Serum P concentrations were evaluated using blood samples obtained 117-119 hours after the first IM-P administration and 21±2 hours after the last IM-P administration. Patients with serum P concentrations <20.6 ng/ml on the ET day were administrated 400 mg vaginal progesterone for rescue. Results: Demographic and cycle characteristics were similar between patients receiving rescue vaginal P (embryo transfer (ET)-day P concentration < 20.6 ng/ml) and patients who did not need rescue vaginal P (ET-day P concentration ≥ 20.6 ng/ml). Clinical pregnancy, miscarriage, and live birth rates were similar between two groups: 52.9%(45/85) vs 59.6%(326/552), p=0.287; 11.1%(5/45) vs 14.1%(46/326), p=0.583; and 47.1%(40/85) vs 50.7%(280/552), p=0.526, respectively. Logistic regression analysis revealed that the female age (p = 0.008, OR=0.942, 95% CI = 0.902–0.984) and embryo quality (ref: good quality for moderate: p=0.02, OR=0.469, 95% CI =0.269–0.760; for poor: p=0.013, OR= 0.269, 95% CI = 0.092–0.757) were independent variables for live birth. Following rescue protocol implementation, ET-day P concentration was not a significant predictor of live birth. Conclusions: Rescue vaginal P administration for low ET day serum P concentrations following IM-P yields comparable live birth rates. Keywords: Hormone replacement therapy, Frozen embryo transfer, Intramuscular progesterone, Luteal phase support, Rescue progesterone